Mother -Infant relationship with mothers suffering from anxiety and mood amendment - Ramalho, Sónia (2014)
Introduction: Safety, protection and emotional regulation are key aspects for constructing mother-child relationships. Therefore, the postpartum period is critical to early promote this relationship. Objective: To describe the feelings and experiences of mothers presenting anxiety and mood alterations and their relationships with the newborn. Methods: Cross-sectional descriptive study. Application of the "Observation Mother-Baby" grid to 44 postpartum women interned in a midwifery service. Results: The puerperal group had a mean age of 31.7 years; 79.5% were married and 45.5% rural residents. The percentage of women without obstetric history was of 59.1% and 52.3 % had normal deliveries. The proportion of primiparous women was of 47.7%, and in 88.6% of the cases, mothers were accompanied by the husband or the baby's father. Somatic complaints were reported in 93.1% of the cases, along with anxiety (54.5%), tearfulness (40.9%), lack of affection (34%), and 54.5% of the women reported fear of being unable to provide baby care. Poor communication was presented by 59.0% of the mothers, whereas only 56.8% would carry the baby, and 47.7% showed head and facial movements. Among the group, 52.2% presented a tense facial expression and 36.3% sorrow. Regarding the concern with the baby, 65% responded to the requests, 25% exaggerated and 13% ignored the requests of the baby. Conclusions: Women with mood swings and anxiety deserve priority intervention for emotional and psychological support. During the transition to parenthood, nurses can promote and oversee the mother-infant relationship and teach mothers to care for their babies.